Effect of dynamic arterial elastance and assisted fluid management software guided resuscitation in septic shock: Pilot study: Eadyn & AFM software–guided resuscitation in septic shock: Pilot study - Pornawalai, Nuwara; Ratanarat, Ranistha; Viarasilpa, Tanuwong (Clinical Critical Care, 2025)
Background: Hypotension in septic shock patients increases mortality and organ dysfunction risks, which is characterized by vasodilation and fluid loss. Therefore, precise fluid and vasopressor therapy is needed. A new monitoring device (Hemosphere®) using parameters of dynamic arterial elastance (Eadyn) and stroke volume change prediction (∆SVpredict) may safely guide treatment, improving outcomes compared to standard care. Objections: to investigate the benefit of using the assist fluid management and dynamic arterial elastance (AFM-Eadyn) guide resuscitation and vasopressor therapy in septic shock resuscitation for mechanically ventilated patients compared with standard of care. Methods: This randomized, controlled, experimental clinical medical device pilot trial included patients older than 18 years with a diagnosis of sepsis or septic shock in medical ICU with onset of shock in less than 24 hours assigned in a 1:1 ratio to receive the assist fluid management and dynamic arterial elastance (AFM-Eadyn) guide resuscitation and the standard of care. Hypothesis: We hypothesize that AFM-Eadyn guide resuscitation in patients with sepsis-induced hypotension would result in less time to shock reversal compared to the standard of care. Ethics and dissemination: The study protocol was approved by the Siriraj Institutional Review Board with the certificate of approval number Si 895/2567 Trial registration: NCT06937918 (ClinicalTrial.gov ID)